Dermatoglyphics Analysis: Uncover Potential Intelligence and Learning Styles of Learners to determine the Appropriate Learning Media - Supriyadi, Supriyadi; Riyanti, Franciska Anes; Satiyarti, Rina Budi; Kamelia, Marlina (IJIS Edu : Indonesian Journal of Integrated Science Education, 2021)
This study aims to uncover the potential of intelligence and learning styles of learners usingdermatoglyphics analysis. This analysis very important to identify learners' characteristics as a basis forselecting a learning media. This research is descriptive qualitative. The subject of this research werelearners in grade 7th junior high school in Bandar Lampung. The research instrument was a recorderfingerprint reader tool for the pattern. The results shows, learners have the potential intelligence: visual-spatial (42%), logical-mathematical (31%), naturalist (17%), interpersonal (10%); the learning styles: visual(92%), kinesthetic (2%), and audio (0%). Based on the results and it’s associated with characteristics of theconcept structure and function of plants concepts, learning media which recommended: learners withvisual-spatial potential intelligence and visual learning style (V S+V) should use pictures, posters, flipcharts, magazines, modules, and pictorial worksheets; learners type of visual-spatial and kinesthetic (V-S+K) is more appropriate to use original media, torso, image; and learners type of naturalist andkinesthetic (N+K) can be stimulated through direct observation with cruising the nature around approach.In conclusion, dermatoglyphics analysis more accurate and faster than the survey method is often used.Also, by understanding various learners characteristics, teachers can choose the learning media inaccordance with learners needs.